Revitalizing Serwisu Hamutuk: Interfaith Synergy and Social Cohesion on the Indonesia–Timor–Leste Border - Florens Maxi Un Bria; Yofince Abatan; Fransiskus Bustan; Adison Adrianus Sihombing; Joel Sagut (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
The progress of modern times is often viewed as a driving force behind advancements in human life. However, it has also had adverse effects on the development of communal values, cultural traditions, and religious beliefs within local communities that have thrived for generations. This study aims to explore the significance of the local culture and religion of Serwisu Hamutuk in the lives of border communities, examine the socio-economic changes that have contributed to the decline of this practice, and propose a revitalization model for Serwisu Hamutuk that enhances community empowerment in border areas. The research employed descriptive qualitative methods, including participatory observation, in-depth interviews, and documentation studies. Data analysis was conducted using the interactive model of Miles and Huberman, combined with contextual theological interpretation. The findings reveal that the practice of Serwisu Hamutuk has evolved into a semi-transactional form as younger generations adapt to economic pressures. These economic factors pose challenges to maintaining the symbolic and religious meanings associated with the practice, which are crucial for fostering community cohesion among border populations. In homogeneous communities, the significance of Serwisu Hamutuk tends to diminish, whereas in heterogeneous communities, it appears to grow stronger. This study advocates for the revitalization of Serwisu Hamutuk to preserve social solidarity and the religious identity of border communities. Furthermore, it contributes to the fields of cultural and religious studies by offering an empowerment model rooted in local wisdom and religious values, integrating both customary and religious authority, and ultimately fostering harmony in communal living.